A Survey on the Investigation and Analysis for a Power System (Micro- Grid) with Stochastic Harmonic Distortion of Multiple Converters - Kuralkar, Vaishali P.; Khampariya, Prabodh; Bakre, Shashikant M. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The current study is based on a survey on the exploration and analysis of stochastic harmonic distortion in power systems using multiple converters (Micro-Grid). When Renewable Energy Systems are integrated into EPS, they may create clean energy, fulfill consumer energy needs, and help to protect fossil fuel supplies, which are rapidly dwindling. These renewable energy sources are frequently interconnected to the grid through power converters (Voltage Source Converters) to provide the necessary energy regulation and conversion. However, Voltage Source Converter (VSCs) generates both current and voltage harmonics, has a negative impact on the Power Quality of a small grid and has potential to cause damage or equipment failure. In the face of uncertainties, such as those resulting from design parameter selection or system parameter changes, the amount of harmonic distortion of many VSCs may be greatly influenced and difficult to forecast. When dealing with VSC harmonic distortion levels in the face of uncertainty, it is necessary to use statistical methodologies.